EFFECTIVENESS OF PLAYING ORIGAMI AND PUZZLE IN MOTORIC DEVELOPMENT ON 4 – 5 YEARS OLD CHILDREN AT KEMALA BHAYANGKARI KINDERGARTEN 38 PURWODADI GROBOGAN - Ni Made Sri Budhi Utami; Sutrisno Sutrisno; Sulistyarini Sulistyarini (Universitas An Nuur, 2019)
Background; Fine motor delay is a common problem in pre-school children. Children with fine motor delay in KemalaBhayangkari kindergarten are about 32 children. According Delgado (2016) 12-18% of children's population in developing countries show significant delay in psychomotor ability resulting behavior problems and difficulty in learning process. One of the strategies that can be used to train fine motor development is to play origami and play a puzzle. The purpose of this research is to know effectiveness of playing origami and playing puzzle in fine motor development on 4 â€“ 5 years old children in Kemala Bhayangkari Kindergarten 38 Purwodadi - GroboganMethod; The research design thatwas used in this study was Quasi Experimet with Posttest Only Control Group Design approach. The sampling technique was Probability sampling with random sampling method (simple random sampling) with 32 respondent.Result; Based on the analysis using SPSS 16.0, the average value for development speed after being treated with origami is 6.19 days, while for the speed of development after being treated with puzzle is 8.13 days. In addition, from Mann-Whitney test, Ï value is 0.003 (Î± = 0.05) which shows the difference of effectiveness of playing origami and playing puzzle dealing with the development of fine motor.Conclusion; From the results of the above research it can be concluded that there are differences between the effectiveness of playing origami and playing puzzle dealing with fine motor development onÂ 4-5 years old children.Â Keywords Â Â Â Â Â Â : Origami, Puzzle, Fine Motor Development